ACUTE GASTRODUODENAL BLEEDINGS – FROM STRATEGY TO TREATMENT DECISION - V. K. Gostischev; M. A. Evseev (Сеченовский вестник)
Principles of management of patients with acute gastrointestinal bleedings due to peptic ulcer disease are discussed with emphasis to opportunities of endoscopic haemostasis, antisecretory treatment. Original group of 1408 is analysed, according to the results of this analysis algorithms of haemostasis control and of intervention are shown.